Hydrolysis of pretreated rice straw by an enzyme cocktail comprising acidic xylanase from Aspergillus sp. for bioethanol production. (December 2016) - Thomas, Leya; Parameswaran, Binod; Pandey, Ashok
Abstract: The most crucial enzyme involved in xylan hydrolysis is endoxylanase which cleaves the internal glycosidic bonds of xylan. The aim of this work was to study the production of extracellular xylanase by a locally isolated strain of Aspergillus sp. under solid-state fermentation (SSF) and to evaluate the potential of the enzyme in enzymatic hydrolysis of pretreated rice straw. Xylanase production reached maximum with incubation period (96 h), moisture level (80%), inoculum size (3 × 10 6  spores/mL), pH (4.8), temperature (25 °C), carbon source (wheat bran) and nitrogen source (yeast extract). Under optimized conditions, xylanase production reached to 5059 IU/gds. Crude xylanase was used for supplementing the enzyme cocktail comprising cellulases (Zytex, India), β-glucosidase (In-house) and xylanase (In-house) for the saccharification of alkali-pretreated rice straw to get the maximum reducing sugar production. The cocktail containing the three enzymes resulted a maximum of 574.8 mg/g of total reducing sugars in comparison to 430.2 mg/g sugars by the cocktail without xylanase. These results proved that the crude xylanase preparation from Aspergillus sp. could be a potent candidate for the enzyme cocktail preparation for biomass hydrolysis in lignocellulosic bioethanol program. Highlights: Production of acidic xylanase by Aspergillus sp. Potential of the enzyme in enzymatic hydrolysis of pretreated rice straw. wheat bran (WB) was found as the best carbon source for xylanase production.